Constant support of physical calculations subsystem of in-core monitoring system “Voyage” - V. V. Galchenko; A. A. Mishin; I. I. Shlapak (Ядерна фізика та енергетика)
In this study a brief description of the polynomial interpolation of few-group constants on sparse grids for VVER-1000 reactor is adduced. The calculations about various burnup instances were made for the method. Besides, comparative analysis of the irregularity factor of kv и kq calculation was made with the help of the preparation of constants by using this method while arranging by different software products.